2001
DOI: 10.1021/jp0023359
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Reactions of H Atoms With Methane and Chlorinated Methanes

Abstract: The reactions of H atoms with methane, four chlorinated methanes, and isobutene have been studied experimentally using the discharge flow/resonance fluorescence technique over wide ranges of temperatures. The rate constants were obtained in direct experiments as functions of temperature. The experimentally obtained activation energies of the reactions of H atoms with chlorinated methanes demonstrate a correlation with the enthalpies of the reactions. Transition state theory reaction models were created on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
90
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(115 citation statements)
references
References 66 publications
24
90
1
Order By: Relevance
“…1. These values agree with previous theoretical results [12][13][14] in the common temperature range, the largest differences being with Knyazev's results [13]. Note that experimental data are not available for these reactions, and only the overall rate constants are known, i.e., the sum of the two channels.…”
Section: Resultssupporting
confidence: 91%
“…1. These values agree with previous theoretical results [12][13][14] in the common temperature range, the largest differences being with Knyazev's results [13]. Note that experimental data are not available for these reactions, and only the overall rate constants are known, i.e., the sum of the two channels.…”
Section: Resultssupporting
confidence: 91%
“…These discrepancies can be attributed at the interference caused by secondary reactions in the experiment that tends to consume the molecular reactant as well as H atoms, as previously discussed by Bryukov et al 6 Finally, the computed overall rate constants for the reaction of H atoms with CCl 4 were found to be systematically higher than those measured by Bryukov et al 6 by a factor of 2.5 ( Figure 5). However, over the temperature range (300-900 K), the slope (-E a /R) of our predicted Arrhenius plot (-2985 K) is very close to the experimental one reported in ref 6 (-2937 K).…”
Section: Geometric Parameters and Vibrational Frequenciesmentioning
confidence: 51%
“…Berry et al 12 reported low level calculations using the G2(MP2) and the semiempirical BAC-MP4 approach to compute rate constants in the temperature range 298-2500 K for the reaction CHF 3 + H f products. Takahashi et al 9 performed G2(MP2) calculations adjusting the barriers to their experimental data in order to predict rate constants for all elementary reactions in the temperature range 1100-1350 K. More recently, Maity et al 13 6 In this work, highly correlated ab initio quantum chemical calculations were performed in order to directly compute the reaction barriers for the title reactions without any further adjustments of the energy. The energetics of these reactions was used together with TST calculations to compute rate constants in the temperature range 300-2500 K. For all of the reactions, all possible elementary pathways are computed and their relative importance under thermal oxidation and combustion conditions (700-2500 K) are discussed.…”
Section: Introductionmentioning
confidence: 99%
“…1 The rate coefficient of the reaction is well known over a large temperature range. [2][3][4][5][6][7][8] It has also served as a benchmark for understanding bimolecular reaction dynamics involving polyatomic molecules. [9][10][11] Due to the involvement of light hydrogenic atoms, the reaction is intrinsically quantum mechanical.…”
Section: Introductionmentioning
confidence: 99%